Description of teachers' knowledge on the occurrence of syncope in State Junior School 1 kabila bone - Haslinda Damansyah; Ani Retni (PSPP JOURNALS, 2022)
Syncope is an event of loss of consciousness and strength of a person's body that occurs from nowhere or without realizing it. The purpose of this study was to determine the description of the teacher's knowledge of the occurrence of syncope. This study uses a qualitative research design with analytical descriptive method. With as many as 5 informants’ teachers. This study uses data collection procedures by conducting observations, interviews and documentation. The procedure for checking the validity of the data uses peer discussion. Based on the results of research and interviews, it was found that, according to the informants, the description of the teacher's knowledge of syncope events is being able to know, understand, apply, analyze and evaluate syncope events that occur among students at school.